Maternal and Neonatal Health Outcome of Childbirth in a Birthing Center, Kathmandu - Kawaya, Nani Maiya; Rana, Muna (Journal of Nursing Education of Nepal, 2023)
Government of Nepal has strategy to establish birthing center in each health facilities to provide  maternal and newborn care to decrease maternal and neonatal morbidity and mortality. This study  was conducted to find out the maternal and neonatal health outcome of childbirth in birthing center  of Paropakar Maternity and Women’s Hospital (PMWH). A descriptive research design was used  .The study population was women admitted for delivery at a birthing center. The purposive sampling  technique was used with sample size 174. Data was collected by using structured interview schedule  and record review of maternal and neonatal outcome from medical record. Data were coded and  entered into statistical Package for the Social Sciences, version 18 and frequency, percentage, mean  and standard deviation for descriptive and chi- square, fisher’s exact and spearman’s correlation for  inferential statistical were used. The women, who were less than 20 years of age, primi and literate had higher rate of perineal injuries  than the women who were more than 20 years, multiparous and illiterate. The babies of primi mother  received lower APGAR score than multiparious mother.  The findings revealed that half (50%) of women had spontaneous labor, majorities (89.1%) of women  had spontaneous vaginal delivery. More than half (53.6%) of women were given episiotomy and least  (1.2%) of the women had complication in third stage of labor. About eight percentage of newborns  required newborn resuscitation and admission to NICU was 4.2%. The study found that the multiparous  women had higher rate of spontaneous labor than primi women.  In conclusion, the women delivering in birthing center had fewer maternal and neonatal complications.  Thus this finding signifies the need to development of nurses- led birthing center in the country to  provide services closer to community.
Keywords: Maternal and Neonatal Health out Come; Childbirth; Birthing Center